Development of software for PC-based machine vision / Muhammad Azmi Ayub - Ayub, Muhammad Azmi (1995)
The aim of this project is to develop a computer program for an automated inspection process. Three main inspection techniques have been developed; 1. Pixel-by-pixel subtraction technique 2. Histogram Technique 3. Circular Background Technique. All these techniques are general purposed techniques that can inspect manufactured products on a production line. The concept and logic behind each technique are also explained. The critical factors governing the success of this system in a production-line are also highlighted. The performance and accuracy of the program have been evaluated. Finally, several recommendations have been suggested for future development of the program.